In-situ Small-Angle X-ray Scattering Investigation of Transient Nanostructure of Multi-phase Polymer Materials Under Mechanical Deformation - Zeinolebadi, Ahmad; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The results in this dissertation set the ground to answer a fundamental question in data-driven polymer material science: "Why don't prepared composites show less fatigue than the pure plastics?" A simultaneous analysis of mechanical testing and small angle X-Ray scattering from the DESY source in Hamburg has been applied to approach this question, which is also central to the European research project "Nanotough", and the results are clearly presented in this book. The evolution of the materials structure is visualized and quantitatively analyzed from exhaustive sequences of scattering images. Three different classes of polymer composites are presented as typical and illustrative examples. The obtained results illustrate that the interactions of their components can cause unpredictable structural effects, ultimaltely leading to a weakening of the material, where a reinforcement was expected.
Introduction -- Experimental Part -- Data Evaluation -- Thermoplastic Polyurethane Elastomers Under Uniaxial Deformation -- Polypropylene/Montmorillonite Nanocomposites: Continuous Stretching and Load-Cycling -- HDPE/PA Microfibrillar Composites Under Load-Cycling -- Summary and Future Works.
Keywords: Polymers .; Materials science; Condensed matter; Ceramics; Glass; Composites (Materials).; Composite materials; Polymer Sciences; Characterization and Evaluation of Materials; Condensed Matter Physics; Ceramics, Glass, Composites, Natural Materials